Law No. 91 of the Year 2018 on Amending some Provisions of the Law on the Protection of Antiquities, Promulgated by Law No. 117 of the Year 1983 = قانون رقم 91 لسنة 2018 بتعديل بعض أحكام قانون حماية الآثار الصادر بالقانون رقم 117 لسنة 1983 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic